2014
DOI: 10.5194/os-10-1013-2014
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the mixed-layer depth in the Northeast Atlantic: an ensemble approach, with uncertainties based on data from operational ocean forecasting systems

Abstract: Abstract. Operational systems operated by Mercator Ocean provide daily ocean forecasts, and combining these forecasts we can produce ensemble forecast and uncertainty estimates. This study focuses on the mixed-layer depth in the Northeast Atlantic near the Porcupine Abyssal Plain for May 2013. This period is of interest for several reasons: (1) four Mercator Ocean operational systems provide daily forecasts at a horizontal resolution of 1/4, 1/12 and 1/36 • with different physics; (2) glider deployment under t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…As described in Lellouche et al (2013), the evaluation of such systems includes routine verification against assimilated and independent in situ and satellite observations, as well as a careful check of many physical processes (e.g., mixed layer depth evaluation as shown in Drillet et al, 2014). Scientific studies brought precious additional evaluation feedbacks (Juza et al, 2015;Smith et al, 2016;Estournel et al, 2016). Finally, several studies showed the added value of surface current analyses provided by these systems for drift applications (Scott et al, 2012;Drevillon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As described in Lellouche et al (2013), the evaluation of such systems includes routine verification against assimilated and independent in situ and satellite observations, as well as a careful check of many physical processes (e.g., mixed layer depth evaluation as shown in Drillet et al, 2014). Scientific studies brought precious additional evaluation feedbacks (Juza et al, 2015;Smith et al, 2016;Estournel et al, 2016). Finally, several studies showed the added value of surface current analyses provided by these systems for drift applications (Scott et al, 2012;Drevillon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During the same period, operational and research oceanic models were run and some of their outputs were used. For estimating large‐scale geostrophic advections of temperature and salinity as well as horizontal Ekman advection of salinity, we used outputs of the operational MERCATOR PSY2V4R4 model [ Drillet et al ., ] (see sections 3.2.2 and 3.2.3). Moreover, for evaluating the heat budget closure presented in section 5.3, the MEDRYS reanalysis [ Hamon et al ., ] and some outputs of the mesoscale research SYMPHONY [ Marsaleix et al ., ] and MARS3D [ Garreau et al ., ] models were also used.…”
Section: Data Used and Forcingsmentioning
confidence: 99%